CURRICULUM DEVELOPMENT AND THE ASSESSMENT OF STUDENT LEARNING: AN EXAMPLE FROM THE WORK-ENERGY AND IMPULSEMOMENTUM THEOREMS - McDermott, Lillian C. (Investigações em Ensino de Ciências, 2016)
The issue of how to assess learning is addressed in the context of an investigation of student understanding of the work-energy and impulse-momentum theorems. Evidence is presented that conceptual and reasoning difficulties with this material extend from the introductory to the graduate level and beyond. A description is given of the development of an instructional sequence designed to help students improve their ability to apply the theorems to real motions. The results from this study demonstrate the need to probe for the reasons behind the answers that students give. Questions that require students to explain their reasoning are necessary. Implications for the preparation of teaching assistants are discussed.